Transforming Learning Support in ODFL: The LESS model - Lynnette Patricia Brice; Alison Harrison; Alan Cadwallader (Flexible Learning Association of New Zealand, 2023)
The purpose of this paper is to share insights gained from the discovery, design, and delivery phases of creating a three-tiered model of non-academic learning support in ODFL, "Learner Engagement & Success Services (LESS)," at Open Polytechnic | Te Pūkenga, New Zealand.  Presented as a case-study, this paper discusses the early vision of the model, examines theoretical understandings related to learner support and engagement, and describes the successes and challenges faced in bringing this vision to reality.  It outlines challenges related to the emergent use of learning analytics (LA) in identifying "exception" learners, the contestability of ethical use and choices of data, and the rapid evolution and devolution of commercially available solution tools.  The tiered model is described as a scalable blend of human and technology enabled interventions and services, underpinned by the values of agency and equity.  The component parts of this model are replicable, and its success is measurable.